Neusachliche Angestellten-Lyrik von Tucholsky, Kästner und Kaléko - Gabriele Sander (Recherches Germaniques)
Since the mid-twenties the poetry of the New Objectivity has brought the everyday reality of white-collar workers increasingly into focus. Kurt Tucholsky, Erich Kästner and Mascha Kaléko, in particular, actively participated with their poems in the discourse on Weimar Republic’s white-collar workers and even anticipated some findings of Kracauer’s famous study Die Angestellten. Their lyrical texts provide not only realistic insights into the contemporary world of work with its hierarchical and authoritarian structures, routines, constraints and mechanisms of exploitation and control but also pointedly express the everyday worries and existential miseries of white-collar workers. Analogous to the new-objectivist novels of the late Weimar Republic, which depict in detail on the basis of individual characters modern professional life including its dark sides, female white-collar workers are also often at the center of poems by Tucholsky, Kästner and Kaléko, pointing out, as under a burning glass, their often sad everyday lives and showing the limits of emancipation.